Faktor-faktor Yang Mempengaruhi Permintaan Bawang Merah Di Kota Medan - Siti Nur Arafah; Yusniar Lubis; Faoeza Hafiz Saragih (Program Studi Agribisnis Fakultas Pertanian Universitas Samudra, 2019)
Shallot is a horticultural commodity classified as vegetable spices that serve as a seasoning for food and traditional medicine. The importance of shallot for cooking makes the demand for shallot continue to increase every year. This research aims to see what factors influence the demand for shallot in Medan City. This research was conducted in Medan Deli Market and Kemiri Market. Sampling used this research used the Accidental Sampling method, which determines the sample based on people who are accidentally encountered in the study area. The number of samples examined in this research is 40 samples of shallot consumers. This research uses Best Linear Unbiased Estimation and Multiple Linear Regression methods. The variables studied were the price of shallot, the income of consumers, the number of family members and the price of yellow onion. The result of this research indicates that the factor that influences the demand for shallot is the price of shallot, the income of consumers and the number of family members, while those that do not affect is the price of yellow onion.